The Politics of Gratitude : Scale, Place & Community in a Global Age - Mitchell, Mark T. (Book collections on Project MUSE., 2012)
In this postpartisan call to action, political theorist Mark T. Mitchell develops the concept of the "politics of gratitude," which revolves around four ideas: creatureliness, gratitude, human scale, and place, culminating in a distinctive, fruitful view of human nature and community at odds with the prevailing norms of individualism (and, not so paradoxically, statism), giantism, and hypermobility. Going beyond the liberal-conservative factionalism that has reduced our political and cultural discourse to clichTs and vitriol, he urges us to become responsible stewards of the earth who are committed to family and community and who abide in gratitude, taking nothing for granted. The result is a political and cultural vision that is at once local, limited, modest, republican, green-and grateful. --Book Jacket.